Resistant starches from dietary pulses improve neurocognitive health via gut-microbiome-brain axis in aged mice - Kadyan, Saurabh; Park, Gwoncheol; Hochuli, Nathaniel; Miller, Katelyn; Wang, Bo; Nagpal, Ravinder (Frontiers in Nutrition, 2024)
Cognitive decline is a common consequence of aging. Dietary patterns that lack fibers and are high in saturated fats worsen cognitive impairment by triggering pro-inflammatory pathways and metabolic dysfunctions. Emerging evidence highlights the neurocognitive benefits of fiber-rich diets and the crucial role of gut-microbiome-brain signaling. However, the mechanisms of this diet-microbiome-brain regulation remain largely unclear. Accordingly, we herein investigated the unexplored neuroprotective mechanisms of dietary pulses-derived resistant starch (RS) in improving aging-associated neurocognitive function in an aged (60-weeks old) murine model carrying a human microbiome. Following 20-weeks dietary regimen which included a westernstyle diet without (control; CTL) or with 5% w/w fortification with RS from pinto beans (PTB), black-eyed-peas (BEP), lentils (LEN), chickpeas (CKP), or inulin fiber (INU), we find that RS, particularly from LEN, ameliorate the cognitive impairments induced by western diet.Mechanistically, RS-mediated improvements in neurocognitive assessments are attributed to positive remodeling of the gut microbiome-metabolome arrays, which include increased shortchain fatty acids and reduced branched-chain amino acids levels. This microbiome-metabolitebrain signaling cascade represses neuroinflammation, cellular senescence, and serum leptin/insulin levels, while enhancing lipid metabolism through improved hepatic function. Altogether, the data demonstrate the prebiotic effects of RS in improving neurocognitive function via modulating the gut-brain axis.